A survey of Eupithecia Curtis, 1825 (Lepidoptera, Geometridae, Larentiinae) in Mongolia with descriptions of two new species - Mironov, Vladimir; Galsworthy, Anthony (Zootaxa, 2014)
The Eupithecia fauna of Mongolia is surveyed in this paper, drawing on previous publications and newly collected material. In total 57 species are recorded. Two species Eupithecia anikini Mironov & Galsworthy, sp. n. and Eupithecia munguata Mironov & Galsworthy, sp. n. are described as new. Twelve species are recorded as new for the fauna of Mongolia, E. olgae, E. illaborata, E. bastelbergeri, E. pusillata, E. actaeata, E. vicariata, E. saisanaria, E. simpliciata, E. impolita, E. assimilata, E. thalictrata and E. exactata. Habitus and genitalia are illustrated for new species, and for little known older species where illustrations are not available in recent papers. A further 2 previously described species are synonymised, E. mongolica Vojnits of E. satyrata Hübner, and E. procera Vojnits of E. exactata Staudinger.